Desempenho acadêmico de estudantes com diagnóstico de transtorno do déficit de atenção e hiperatividade (TDAH) em uso de metilfenidato: revisão sistemática - Joyce Costa Melgaco de Faria (2017)
Introduction: Attention deficit hyperactivity disorder (ADHD) is defined as a disorder in which the persistence of symptoms of inattention, hyperactivity and impulsivity interfere negatively in individuals´ social, academic and professional outcomes. Impaired academic achievement is one of the main reasons for starting ADHD medication. Among the available pharmacological options, methylphenidate is the drug most commonly prescribed. Objective: To evaluate the evidence of the effectiveness of methylphenidate in improving the academic performance of ADHD students. Methods: Systematic review of observational studies. Results: Three cohorts, two before-and-after designs and two crosssectional studies were included in the review. They involved 366 children or adolescents aged 6 to 18 years. The methylphenidate dosages ranged from 10 to 72 mg/day and the treatment duration from 2.6 months to 4.25 years. In five out of seven studies, it was concluded that methylphenidate leads to improvement in academic performance. However, among the four lowest bias risk studies (highest scores on the Newcastle Ottawa scale), three have concluded that the drug is ineffective for this purpose. Four studies assessed the long-term use of methylphenidate (more than one year) and the only one which indicated methylphenidate is effective obtained the lowest score on the Newcastle-Ottawa scale. The included studies have considerable limitations and great heterogeneity regarding methodological design and academic performance measurement criteria. Conclusion: Although there are studies indicating that short-term use of methylphenidate may improve outcomes in the school environment, the evidence is weak. The available scientific literature does not support the establishment of adequate conclusions about the real benefits of methylphenidate in the academic improvement of ADHD students.